Politik Hukum Hindia Belanda dan Pengaruhnya Terhadap Legislasi Hukum Islam di Indonesia - Muhammad Iqbal (Universitas Islam Negeri Jakarta, 2012)
Abstract: The Influence of Dutch East Indies Politics and Law on Islamic Law Legislation in Indonesia. Dutch East Indies politics and law is based on the interests of Dutch colonialism in Indonesia. At the start, the Dutch exercised a compromising brand of politics and law, however this was less than advantageous. Then, in its growth, the Dutch executed confrontational politics and law, which, evidently, was effective in swaying their power. Afterwards, Indonesia became independent in 1945. It turns out that confrontational thinking, as exhibited in the politics and law of the Dutch East Indies, had an influence on the Indonesian nation. They often rejected efforts to legislate Islamic law into the national legal system for a number of types of reasons. This article aims to examine the progression of Dutch colonial politics and law and its influence on the production of Indonesian Islamic politics and law over the course of independence.Keywords: law and politics, Islamic law, Adat law, Dutch East Indies, conflictAbstrak: Politik Hukum Hindia Belanda dan Pengaruhnya Terhadap Legislasi Hukum Islam di Indonesia. Politik hukum Hindia Belanda didasarkan pada kepentingan penjajahan mereka atas Nusantara (Indonesia). Pada awalnya Belanda menempuh politik hukum kompromistis, namun kurang menguntungkan. Lalu, dalam perkembangannya Belanda menjalankan politik hukum konfrontatif yang ternyata efektif dalam melanggengkan kekuasaan mereka. Setelah Indonesia merdeka 1945, ternyata cara berpikir konfrontatif seperti dalam politik hukum Hindia Belanda berpengaruh bagi sebagian bangsa Indonesia. Sering mereka menolak upaya legislasi hukum Islam ke sistem hukum nasional dengan pelbagai macam alasan. Tulisan ini berupaya mengelaborasi perjalanan politik hukum penjajah Belanda dan pengaruhnya dalam perkembangan politik hukum Islam Indonesia pada masa kemerdekaan.Kata Kunci: politik hukum, hukum Islam, hukum adat, Hindia Belanda, konflikDOI: 10.15408/ajis.v12i1.972